The reality of psychological defense deception among students practicing sports in the faculties of physical education and Sports Sciences/Baghdad University - Sawsan Jawdat; Dr. Najlaa Abbas (الرياضة المعاصرة)
The study aimed to apply the measure of psychological defense deception for university students practices for sports, and to recognize the level of psychological defense deception among university students practices for sports, and the researchers adopted the descriptive curriculum by the survey method  a sample of third-graders in the Faculties of Physical Education and Sports Sciences /Baghdad University for the academic year (2020-2021) and the number of the students are (209) students, selected from them (189) students by (90.43%) In the random way of the main application sample, also (10) students were selected by (4,785%) in a random way of the exploration experiment sample, a recent specialized measure were adopted by the two researchers for the target sample of measurement, and the procedures were from a exploration experiment and a major survey in the research for the period between (2/3/2021 and 6/4/2021), as after the application of the measure by conducting the main survey they were mediated by paper forms,  and the results were addressed by the statistical bag system (SPSS) (V26) to be the conclusions and recommendations that university students practice sports have an acceptable level of psychological defense deception, and need to raise the recommended level of compensation and projection of Psychological defense deception are characterized by surpassing, and it is necessary to increase interest in the mechanisms to encourage university students to exercise in student activities with the availability of reinforcement of various kinds, and it is necessary for the Ministry of Higher Education and Scientific Research to ensure sports culture and its role in the psychology of female students in education courses Continuous and electronic activity platforms to communicate between faculty members